Therapeutic potential of ginseng in the treatment of allergic respiratory diseases - Szewczyk, Wiktoria; Żychowska, Gabriela; Sowa, Florian; Dederko, Magdalena; Drapała, Justyna; Mucha, Kamil; Gomułka, Krzysztof (Quality in Sport, 2026)
Introduction and Purpose: Ginseng (Panax spp), known as the king of herbs, is one of the most important medicinal plants in East Asia. Its several thousand years of history in medicine is due to its various therapeutic properties, including immunomodulatory and anticancer properties. The aim of this paper is to present the effects of ginseng use on reducing the symptoms of allergic respiratory diseases, which are becoming increasingly common in the population, as described in scientific studies State of knowledge: Animal studies have shown that Panax ginseng reduces inflammation of the respiratory tract through its anti-inflammatory and immunomodulatory effects on immune system cells. The effectiveness of black ginseng extract in studies on mice was comparable to that of dexamethasone. Korean red ginseng extract showed similar biological activity, alleviating asthma symptoms and reducing allergic inflammatory reactions in the nose, as well as acting as an antioxidant to reduce inflammation. Human studies have shown that red ginseng extract acts similarly to antihistamines, relieving itching of the nose and eyes, reducing nasal discharge, and reducing nasal congestion. Important medicinal components of the plant are ginsenosides, which can, among other things, reduce the number of inflammatory response cells and suppress cytokine expression, thereby reducing allergy symptoms. Conclusions: Ginseng shows promising results in the treatment of allergic respiratory diseases by reducing the severity of clinical symptoms and decreasing inflammatory response indicators. It is worth noting that despite good results, further research on a larger group of patients is still needed to confirm its efficacy and safety.